Insight as a mechanism of change in dynamic therapy for major depressive disorder - Jennissen, Simone; Connolly Gibbons, Mary Beth; Crits-Christoph, Paul; Schauenburg, Henning; Dinger, Ulrike (Journal of counseling psychology, 2021)
This study aimed to investigate change in insight into maladaptive interpersonal patterns over the course of psychotherapy, as well as the specificity of insight as a change mechanism in dynamic treatments. A total of 100 patients received up to 16 sessions of either cognitive or dynamic therapy for major depressive disorder in a randomized clinical trial. Assessments of insight (Insight into Conflictual Relationship Patterns scale) and depression severity (Hamilton Depression Inventory) took place at the beginning of treatment, at month 2, and month 5. Patient insight significantly improved over the course of dynamic treatments. Gains in insight from the beginning to month 2 of treatment were a significant predictor of decreases of depressive symptoms from month 2 to month 5 of treatment in the dynamic, but not in the cognitive treatment group, despite a nonsignificant interaction. Results provide support for insight as a change factor in dynamic therapies. Better self-understanding of dysfunctional interaction patterns could help patients to find more adaptive ways of behaving, to form more satisfying relationships, and to improve their depression. (PsycInfo Database Record (c) 2021 APA, all rights reserved).